Co-opportunity : join up for a sustainable, resilient, prosperous world - Grant, John, 1964- (John Wiley, 2010)
John Grant is back! Bestselling author of Green Marketing Manifesto fame returns to get you involved in creating a sustainable future!. In this book, green business guru John Grant shows how we, when we join forces through co-operative initiatives, can really make changes and work towards a better future. John uses cases and examples from around the world, from social networks to social ventures, Carrot Mobbing to the Carbon Disclosure Project, to show how a move to greater co-operation via what he calls Co-operative Networks can be a way forwards for all of us to increase the common well-being.